RAY JOHNSON'S ANTI-ARCHIVE: blackface, sadomasochism, and the racial and sexual imagination of pop art. Issue 1 (2nd January 2018) - Kahan, Benjamin
Abstract: This essay explores the work of "New York's most famous unknown artist, " Ray Johnson, contending that his complex relationship to sadomasochism provides a key switch point for Pop's sexual and racial imaginary. In the register of sex, Johnson's sadomasochism contests the stability of the relationship between homosexuality and Pop (theorized by Kenneth E. Silver, Jonathan D. Katz, Richard Meyer, and Douglas Crimp), offering instead a queerer object that opens out new models of collaborative artistic production. In the register of race, sadomasochism enables Johnson to articulate a monochrome world (particularly in relation to the blackface of his bunny portraits), attempting to void the binarized color-line's fissuring force. While this strategy from our contemporary vantage feels politically suspect, I see it is part of a larger project of political and social reparation whereby the explicitly sadomasochistic themes of Johnson's work imagine a rebuttal to and reconfiguration of the racist exclusionary forces of the art world.